The Effect of Compensation, Transformational Leadership on Employee Commitment through Job Satisfaction as a Mediating Variable - Dewi Astuti; Zulkifli Musanip Siregar; Rizki Syahputra (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The study aims to determine the effect of Compensation, Transformational Leadership on Commitment through Employee Job Satisfaction. This research was conducted at the Office of the Head of Bandar Tinggi Village, Bilah Hulu District, Labuhanbatu Regency. Data processing uses IBM SPSS Statistics 26. The data analysis technique used is the path analysis technique. The number of samples used in this study was 30 people. Sampling based on saturated sampling technique. Data collection was carried out by distributing questionnaires and interviews. Based on the research that has been done, it can be concluded that compensation and transformational leadership has a significant effect on commitment through job satisfaction. From the results of the compensation test, it has a significant effect with a value of 0.03 (<0.05). Transformational leadership has a significant effect with a significant value of 0.000 (<0.05). Indirect compensation has a significant effect with a value of 0.208 while the direct effect is -0.204. Transformational leadership also has a significant influence indirectly giving a value of 0.570 and a direct influence of -0.224.